POTENTIAL OF CATTLE FEED FROM PALM OIL LEAVES AND MIDRIBS USING THE FERMENTATION PROCESS IN WEST KALIMANTAN - Ely Nurhidayati; Marcelina Marcelina; Fitriah Fitriah; Ratih Rahmawati; Febri Prima; Duta Setiawan (Universitas Muhammadiyah Mataram, 2024)
Abstract: One of the most crucial phases of cattle farming is the supply of high-quality animal feed, which can enhance productivity and animal health. Animal feed is often a problem in West Kalimantan. However, this area is an oil palm plantation, so it has the potential to produce oil palm waste. This community service activity aims to increase knowledge and practice community skills in oil palm plantations in utilizing palm oil waste in cattle feed. The community service applied a socialization and training methods to make high-quality fermented animal feed using palm oil waste, namely leaves and fronds. Participants in this program included the village chief and the village's livestock owners, a total of 30 people. The farmers benefited from the results of this training and socialization. The villagers can use palm leaves and fronds to make fermented animal feed. This adds insight into how to improve livestock productivity and health. In addition, this activity also has the potential to reduce the amount of palm oil waste generated, in addition to increasing the economic value of the waste. The results of the feed processing technology service activities after socialization and training were carried out, there was an increase in participants' knowledge regarding understanding feed processing, post-test scores from 33% to 80% after the post-test, and post-test scores on feed processing practices from 40% to 80% after the post-test.